MODEL PENGELOLAAN SAMPAH DI KABUPATEN TULANG BAWANG - Ade Iskandar; Rahim Doli Patuan Sakti Siregar (e-JKPP, 2019)
Waste and its management are now becoming increasingly pressing problems in cities in Indonesia, because if not done properly handling will result in adverse changes in the environmental balance that pollutes the environment both to soil, water, and air. The problem that often arises for the community is the lack of technical knowledge on how to manage waste or recycle waste. Lack of knowledge about managing waste experienced by the community has resulted in a high and significant buildup of waste. Supposedly, waste management in the world is no longer a new thing that requires attention for every community, moreover the waste generated from the community and indeed should be an obligation for the community itself to manage it in addition to using services from the government. Attitudes and community participation as well as government assistance (technical and non-technical) in various forms are needed to accelerate the development and growth of community-based settlement waste management with the principle of 3 R (Reduced, Reused and Recycled). The purpose of this study is to find out, analyze, and study how the Waste Management Model in Tulang Bawang District involves community participation so that the waste can be managed properly. In this study the authors used a qualitative data analysis with a descriptive approach, the data collection methods in this study were observation, interviews, and documentation. In general, the results of this study are as follows : (1) The model of waste management with the principle of 3 R through waste segregation activities is a paradigmatic solution, which is a solution from the paradigm of how to manage waste; (2) Community Empowerment in the role of RT / RW management is very large in helping to realize the program and bridging communication between the local government and the community; (3) The government together with the RT / RW management and management can Participate in providing planned and measurable education to the public about proper waste management.